Identifikasi Jenis Batuan Panas Bumi Di Desa Angseri Dan Sekitarnya Dengan Metode Gravitasi - Sukarasa, Ketut; Paramarta, Ida Bagus Alit (Universitas Hamzanwadi, 2023)
The research has been done on 2D model of the subsurface structure of the hot springs in Angseri Village and its surroundings using the gravity method. The purposes of the research is to determine the distribution of gravity anomaly values, density values and subsurface rock structures. The results showed that the value of Bouguer anomaly was between 10-137 mGal, the regional anomaly was between 42-105 mGal, and the residual anomaly was between (-32)-(35) mGal. The modeling results showed that the subsurface structure of the study area was composed of lava rock (1.1-1.73 gr/cm3), tuff (1.61-2.52 gr/cm3), tuff breccia (2.51-2,79 gr/cm3), lava (2.8-2.89 gr/cm3) and volcanic breccia (2.9-3.2 gr/cm3), where volcanic breccia rocks as permeable rocks and tuff breccia rocks as cover rocks.